2020
DOI: 10.3892/etm.2020.9080
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a rat model with ageing insomnia induced by D‑galactosef and para‑chlorophenylalanine

Abstract: The current study aimed to establish a rat model of ageing insomnia induced by D-galactose and/or para-chlorophenylalanine. Following establishment of the model, body weights were measured, and Morris water maze and pentobarbital-induced sleep tests were performed. The serum levels of inflammatory mediators and the neural levels of neurotransmitters were detected. The results demonstrated that the body weights of PCPA+D-gal-induced ageing insomnia rats decreased significantly. Ageing insomnia rats exhibited lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Similarly, IL-6 levels were increased in the rat brain. 57,59–61 Also, molecular docking study revealed high affinity of rutin to IL6RA and IL6RB indicating the ability of rutin to reduce aging-associated inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-6 levels were increased in the rat brain. 57,59–61 Also, molecular docking study revealed high affinity of rutin to IL6RA and IL6RB indicating the ability of rutin to reduce aging-associated inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the potential mechanisms linking insomnia and cognitive impairment, we first established a PCPA-induced insomniac model. Compared with other models, , such as the horizontal platform environmental deprivation method, the stress stimulation sleep deprivation method, the gentle stimulation deprivation method, and the forced exercise deprivation method, our model has a short modeling cycle, clear target, and significant insomnia characteristics and is suitable for acute insomnia studies . Currently, a variety of behavioral tests, including the Morris water maze test, Y-maze test, novel place recognition test, and novel object recognition (NOR) test, have been used to investigate the cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NREM can be retained to a certain degree by the rats adapting flexible postures, rather than the rats only being allowed to sit on the platforms. Secondly, unlike the deep-water design used for multi-platform devices in previous studies ( 34 ), the shallow water allows the rats to walk freely and to communicate or play with each other without getting most of their body wet, which can protect them from developing depression or soaking-associated skin diseases. Thirdly, although the platforms allow the rats to sleep lightly, they may rotate around the steel wire when the balance between the two sides of the platform is distorted during REM sleep.…”
Section: Discussionmentioning
confidence: 99%